(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
INTRODUCTION: Fever and skin rash is a common paediatric complaint which makes the child irritable & leads anxious parents rush to the emergency. Inability to express complaints by patient and varied presentation of common ailments make it difficult for general practitioners to diagnose aetiology of febrile rashes. Thus pediatric dermatology has now been new area of interest for dermatologists and pediatricians. AIMS & OBJECTIVES  To study epidemiological data of febrile skin diseases in pediatric population.To study pattern of association of fever with skin rashes.MATERIAL AND METHOD:A prospective study was conducted in dermatology department of tertiary care centre from June 2017 to May 2019. All paediatric patients with fever and skin rashes were included. Demographic data, history of development of fever, type of fever, duration between fever & development of rash, morphology & distribution of rash was noted. RESULTS:Among 243 patients, 145 were male and 98 were female. Highest incidence was noted in 0-7 year agegroup. Maximum patients belonged to lower lower(37%) socioeconomic class. Similar complaint in siblings was seen in 35% of patients having infectious disease. Maximum patients were of viral exanthema in infectious and allergic reactions in non infectious diseases. Most common system involved was reticuloendothelial followed by respiratory system. CONCLUSION:Proper knowledge of epidemiological trends of regional diseases, association between fever & development of rash and alarming signs of systemic deterioration can help in early diagnosis and intervention hence better outcome.